Clinical and epidemiological characteristics of adult patients diagnosed with extrapulmonary tuberculosis at Hipolito Unanue Hospital in Tacna during the period 2016-2018 - Mamani Loza, Astrid Milagros (2021)
Objective: To know the clinical and epidemiological characteristics of adult patients diagnosed with extrapulmonary tuberculosis at the Hipolito Unanue Hospital in Tacna during the period 2016-2018. Material and methods: Observational, descriptive study. All patients older than 14 year-old with a diagnosis of extrapulmonary tuberculosis were included, data were obtained from clinical records, were processed in the SPSS v24 statistical program, and presented through tables with absolute and relative frequencies. Results: Of 1247 patients diagnosed with tuberculosis, the frequency of extrapulmonary tuberculosis as 9.62 % (120 cases), of which 60.8 % were hospitalized. The patients were characterized mainly by being male (64.2 %), from 20 to 29 year-old (35.8 %), with secondary studies (75 %), from Tacna (74.2 %). 68.33 % had a history of non-modifiable conditions and 25 % had modifiable conditions. 65.83 % of cases involved the respiratory system; 14.17 % involved the enteroperitoneal system; 13.33 % involved the central nervous system; 9.16 % involved the lymphatic system; and 8.33 % involved the tegumentary system. 12.5 % had multisystem tuberculosis. 56.96 % of patients had fever and 34.18 %, weight loss, hyporexia and coughing with expectoration. Conclusion: The pleura was the most frequent location of extrapulmonary tuberculosis, 18.3 % presented pulmonary tuberculosis as a non-modifiable condition, 6.67 % HIV/AIDS and 5 % had diabetes mellitus, asthma and anemia.